2013
DOI: 10.1590/s0103-05822013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Tradução e adaptação cultural da ferramenta Strongkids para triagem do risco de desnutrição em crianças hospitalizadas

Abstract: OBJETIVO: Realizar a tradução para o português e a adaptação cultural da ferramenta para triagem de desnutrição Strongkids, em crianças hospitalizadas. MÉTODOS: Estudo documental no qual foi realizada a tradução da ferramenta da versão original (inglês) para a língua portuguesa. A tradução e a adaptação cultural do conteúdo de tal instrumento consistiram de seis etapas, segundo a metodologia proposta por Beaton et al (tradução inicial, síntese das traduções, retrotradução, verificação do processo de equivalênc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
0
6
0
10
Order By: Relevance
“…The tool was easily understood by health professionals, parents, and/or guardians [46]. Even so, a Brazilian study found that the tool presented moderate sensitivity (60.3%) and low specificity (42.4%) for predicting a body weight loss greater than 2% on hospital discharge [16].…”
Section: Nutritional Screening Tools For Pediatric Patientsmentioning
confidence: 99%
“…The tool was easily understood by health professionals, parents, and/or guardians [46]. Even so, a Brazilian study found that the tool presented moderate sensitivity (60.3%) and low specificity (42.4%) for predicting a body weight loss greater than 2% on hospital discharge [16].…”
Section: Nutritional Screening Tools For Pediatric Patientsmentioning
confidence: 99%
“…The nutritional risk screening tools are extremely important in the hospital environment and should be used at the time of admission, because they can early identify factors that affect nutritional status. 9,19,20 The tools for nutritional screening of patients admitted to the NICC are scarce and, in many situations, those that exist are not suitable for Brazilian NICCs. An example is the Neonatal Nutrition Screening Tool (NNST), which uses a test that checks diastolic flow of the umbilical artery as one of its criteria, a parameter that is not routinely adopted in Brazilian public hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…23 For a screening tool of nutritional risk to be considered adequate, it must: measure what it proposes to assess, be practical, simple, effective, and amenable to application by a health professional, be it a nutritionist, nurse or doctor. 19,24 During the validation process, eight judges participated in the critical analysis of the tool. This is the number recommended in literature, which suggests a minimum of five and a maximum of 10 judges to participate in the validation process.…”
Section: Discussionmentioning
confidence: 99%
“…A desnutrição é uma das doenças nutricionais mais importantes nos países em desenvolvimento devido à sua alta prevalência, aos prejuízos socioeconômicos, à relação com as taxas de mortalidade infantil e, também, tem sido associada ao aumento da morbimortalidade, do tempo de internação e, finalmente, a maiores custos com a hospitalização. [1][2][3][4] Diversos estudos relatam uma alta prevalência da desnutrição na admissão hospitalar infantil e que 15% a 50% das crianças apresentam a piora do estado nutricional durante a internação, porém, ainda são escassas as pesquisas publicadas sobre este assunto. 3,[5][6][7] A triagem de risco nutricional é um método de baixo custo, não invasivo e facilmente aplicável à beira do leito.…”
Section: Introductionunclassified